2016
DOI: 10.1590/0103-5150.029.002.ao06
|View full text |Cite
|
Sign up to set email alerts
|

Diastasis of the rectus abdominis muscle prevalence in postpartum

Abstract: Introduction: Diastasis of the rectus abdominis muscle (DRAM) is characterized by the separation of the rectus abdominis muscles beams, caused by enlargement of the linea alba, a common condition during pregnancy. Physical therapy has been shown necessary in women health, to help them adjust the physical changes throughout the pregnancy and puerperium. Objectives: To verify the DRAM prevalence in the immediate puerperium in a sample of women attended by the Unifi ed Health System in Guarapuava, PR, Brazil, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
1
0
5
Order By: Relevance
“…Although studies have shown that multiparity can predispose a greater separation of muscle fibers from the rectus abdominis during pregnancy, it was observed that most puerperal women were primiparous and all had diastasis. 8 In addition, a higher incidence of supraumbilical abdominal diastasis was evidenced in this study. In agreement with this, it was found in a study that 36% of the population had diastasis at the supraumbical level, due to the disposition of the fetus, and 11% infraumbilical diastasis, as a result of the connection of the abdominal muscles in the shape of the letter V. 9 It is noted in the present study that the performance of physiotherapy to reduce abdominal diastasis in the immediate postpartum period had an excellent impact on the reduction of supraumbilical abdominal diastasis, being statistically relevant (p < 0.001).…”
Section: Resultssupporting
confidence: 56%
“…Although studies have shown that multiparity can predispose a greater separation of muscle fibers from the rectus abdominis during pregnancy, it was observed that most puerperal women were primiparous and all had diastasis. 8 In addition, a higher incidence of supraumbilical abdominal diastasis was evidenced in this study. In agreement with this, it was found in a study that 36% of the population had diastasis at the supraumbical level, due to the disposition of the fetus, and 11% infraumbilical diastasis, as a result of the connection of the abdominal muscles in the shape of the letter V. 9 It is noted in the present study that the performance of physiotherapy to reduce abdominal diastasis in the immediate postpartum period had an excellent impact on the reduction of supraumbilical abdominal diastasis, being statistically relevant (p < 0.001).…”
Section: Resultssupporting
confidence: 56%
“…As tensões impostas nos músculos do tecido e as estruturas da parede abdominal à medida que a gravidez evolui e o útero aumenta de tamanho. O crescimento do útero pode alongar esses músculos como resultado da frouxidão da linha alba e realizando a separação do reto abdominal (DEMARTINI, 2016). Saraiva et al (2019) tratam que dentre essas transformações ocorridas pela diástase do músculo reto abdominal, a mesma vem sendo tratada amplamente pela literatura, podendo ser dada por diversos elementos que vai desde flacidez, obesidade, macrosomia fetal, gestações múltiplas etc.…”
Section: Referencial Teóricounclassified
“…Bu süreç DRA oluşumunu kaçınılmaz kılmaktadır. Aynı zamanda gebeliğin ilerlemesinin linea alba'nın bütünlüğünü etkilediği, bu nedenle DRA'ın üçüncü trimester ve erken doğum sonu dönemde daha yaygın olduğu ileri sürülmektedir (18).…”
Section: Dra Tanımı Ve Görülme Sıklığıunclassified